Effect of row spacing and seeding rate on grain sorghum tolerance of weeds - Hewitt, Cade Alan (Kansas State University, 2015)
Weed control in grain sorghum has always presented a challenge to producers in the semi-arid Great Plains. Cultural control tactics such as narrowing of row spacings and increasing seeding rates can be effective control methods. The objective of this research was to determine the row spacing and seeding rates that maximizes yield while suppressing weeds. Grain sorghum row spacings of 25, 51, and 76-cm and seeding rates of 75,000, 100,000, 125,000, and 150,000 seeds ha[superscript]-1 were evaluated in Kansas at Beloit and Manhattan in 2013 and Beloit, Manhattan, and Hays in 2014. Grain sorghum growth and yield response were measured in response to natural weed communities. After evaluation, Beloit was considered a low weed pressure site while Manhattan and Hays were considered to be moderate and high weed pressure sites, respectively. Grain sorghum biomass was different while weed biomass was consistent across row spacings. Yield loss equations and profit functions were derived to determine the amount of grain yield and $ ha[superscript]-1 loss from each of the three locations. Yield and profit lost was greatest amongst weedy observations. Results indicated that grain sorghum grown on wide row spacings and seeding rates of 125,000 seeds ha[superscript]-1 out yielded all other treatments under a low weed pressure site (Beloit) and narrow row spacings out yielded wider spacings in moderate and high weed pressure sites (Manhattan and Hays). These results imply that a Kansas grain sorghum producer should evaluate potential weed pressure before determining a final row spacing and seeding rate.
Keywords: Row spacing; Seeding rate; Grain sorghum; Weed tolerance; Agronomy (0285)